The Role of Teachers in Developing Poetry Reading Skills at SDIT Cordova 3 Class 4 - Iswandi, Siti Meiliana Syahra; Rakhman, Patra Aghtiar; Rokmanah, Siti (CV. Rayyan Dwi Bharata, 2023)
This research is motivated by the researcher's observations regarding the role of teachers in developing poetry reading skills in class 4 at SDIT Cordova 3. The purpose of this research is to obtain information or an overview of the role of teachers in developing poetry reading skills carried out by SDIT Cordova 3 with the hope of good results. achieved by grade 4 students. This research uses qualitative research using a descriptive approach method by obtaining data from interviews, observation and documentation. Based on the research results, there are several difficulties experienced by students, including lack of self-confidence and lack of motivation. To solve this problem, SDIT Cordova 3 uses the demonstration method so that learning becomes more active and fun.